Preconditioners and Electron Density Optimization in Orbital-Free Density Functional Theory (Communications in Computational Physics, 2012)
Orbital-free density functional theory (OFDFT) is a quantum mechanicalmethod in which the energy of a material depends only on the electron density andionic positions. We examine some popular algorithms for optimizing the electrondensity distribution in OFDFT, explaining their suitability, benchmarking their performance, and suggesting some improvements. We start by describing the constrainedoptimization problem that encompasses electron density optimization. Next, we discuss the line search (including Wolfe conditions) and the nonlinear conjugate gradientand truncated Newton algorithms, as implemented in our open source OFDFT code.We finally focus on preconditioners derived from OFDFT energy functionals. Newly-derived preconditioners are successful for simulation cells of all sizes without regionsof low electron-density and for small simulation cells with such regions.